Race and Socioeconomic Status Differences in Study Abroad Participation: The Role of Habitus, Social Networks, and Cultural Capital. (26th December 2012) - Simon, Jennifer; Ainsworth, James W.
Abstract : This study examines how race and socioeconomic status contribute to disparities in study abroad participation. Our mixed methods approach provides a broad overview of the selection process into study abroad using national data. It also provides a nuanced understanding of the mechanisms that perpetuate inequality among Black and lower class students. Both quantitative and qualitative results show that students' habitus, social networks, and cultural capital shape their study abroad experiences. We find that students with a positive predisposition toward internationalization (having foreign-born parents and/or experiencing different cultures overseas) were more likely to study abroad. Whites and high socioeconomic status students were also more likely to have family and friends who valued study abroad than were lower socioeconomic status and Black students. These advantaged students were better able to acquire and use cultural capital when accessing information from institutional agents. They were also more likely to possess the knowledge and background that complied with institutional standards. These factors contributed significantly to the race and class disparities in study abroad participation. This study contributes to the scant literature on study abroad by revealing mechanisms through which the reproduction of inequality is shaped in the university setting. We argue that patterns found to apply to this process are likely to take place in other processes in higher education as well.